Identification of single major QTL and candidate gene(s) governing hull-less seed trait in pumpkin - Kaur, Barinder; Garcha, Karmvir Singh; Bhatia, Dharminder; Khosa, Jiffinvir Singh; Sharma, Madhu; Mittal, Amandeep; Verma, Neha; Dhatt, Ajmer Singh (Frontiers in Plant Science, 2022)
The hull-less pumpkin (Cucurbita pepo) seed does not require de-hulling prior to use for human consumption, as a result highly preferred by the oil, nut, and baking industries. In hull-less seeds, a single recessive gene is responsible for the absence of outer thick seed coat layers, however, the genomic region and gene(s) controlling the trait are unclear to date. In this study, four crosses attempted to derive F2 and backcross populations confirmed the single recessive gene inheritance of hull-less seed trait in populations adapted to the sub-tropical climate. The candidate genomic region for hull-less seed trait was identified through BSA-QTLseq approach using bulks of F2:3 progenies from a cross of HP111 (hulled) and HLP36 (hull-less). A novel genomic region on chromosome 12 which ranged from 1.80 Mb to 3.86 Mb was found associated with the hull-less seed trait. The re-sequencing data identified a total of 396 SNPs within this region and ten were successfully converted into polymorphic KASP assays. The genotyping of segregating F2 (n=160) with polymorphic KASP assays resulted in 40.3 cM partial linkage map and identified Cp_3430407 (10 cM) and Cp_3498687 (16.1 cM) as flanking markers for hull-less locus (Cphl-1). These flanking markers correspond to 68.28 kb region in the reference genome and the marker, Cp_3430407 successfully predicted the genotype in 93.33% of the C. pepo hull-less germplasm lines, thus can be used for marker assisted selection in parents polymorphic for the hull-less seed trait. The Cphl-1 linked genomic region (2.06 Mb) encompasses a total of 182 genes including secondary cell wall and lignin biosynthesis related transcriptional factors viz., ‘NAC’ (Cp4.1LG12g04350) and ‘MYB’ (Cp4.1LG12g03120). These genes were differentially expressed in the seeds of hulled and hull-less genotypes and therefore could be the potential candidate genes governing the hull-less seed trait in pumpkin.